2018
DOI: 10.5223/pghn.2018.21.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pediatric Patients Presenting with Acute Abdomen Accompanying Dilatation of the Common Bile Duct

Abstract: PurposeThe aim of this study was to describe our treatment experiences with patients who had acute abdomen (AA) with common bile duct (CBD) dilatation.MethodsThe treatment outcomes in children with AA and CBD dilatation were retrospectively reviewed. According to the shape of the intrahepatic bile ducts on ultrasonography (US), the origin of the pain was estimated as choledochal cyst (CC) complication or choledocholithiasis in normal CBD. Patients with complicated CC underwent surgery, and patients with choled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Abdominal pain is the most common symptom (93.8%) [75], especially in older patients and presents with colic pattern which has a variable interval time (between attacks) up to several years. When investigating the cause of CBD dilatation and differential diagnosis of unclear upper abdominal pain, jaundice, and pancreatitis in children, CCs must be considered [76]. Unfortunately, 29-62% of pediatric patients with CC have been reported that they have choledocholithiasis [77,78], that is, distinguishing this two situation (CC-associated choledocholithiasis and -nonassociated choledocholithiasis) may be difficult.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Abdominal pain is the most common symptom (93.8%) [75], especially in older patients and presents with colic pattern which has a variable interval time (between attacks) up to several years. When investigating the cause of CBD dilatation and differential diagnosis of unclear upper abdominal pain, jaundice, and pancreatitis in children, CCs must be considered [76]. Unfortunately, 29-62% of pediatric patients with CC have been reported that they have choledocholithiasis [77,78], that is, distinguishing this two situation (CC-associated choledocholithiasis and -nonassociated choledocholithiasis) may be difficult.…”
Section: Clinical Presentationmentioning
confidence: 99%